Political Economy Analysis - How to note - and DFID (DFID, 2009)
Political economy analysis is a powerful tool for improving the effectiveness of aid. Bridging the traditional concerns of politics and economics, it focuses on how power and resources are distributed and contested in different contexts, and the implications for development outcomes. It gets beneath the formal structures to reveal the underlying interests, incentives and institutions that enable or frustrate change. Such insights are important if we are to advance challenging agendas around governance, economic growth and service delivery, which experience has shown do not lend themselves to technical solutions alone. Political economy analysis is not a magic bullet for the resolution of intractable development problems. However, it can support more effective and politically feasible development strategies, as well as inform more realistic expectations of what can be achieved, and the risks involved. It can also contribute to better results by identifying where the main opportunities and barriers for policy reform exist and how donors can use their programming and influencing tools to promote positive change. This understanding is particularly relevant in fragile and conflict-affected environments where the challenge of building peaceful states and societies is fundamentally political. There are an increasing number of political economy tools available to development agencies for a range of analytical and operational purposes. This note brings together this material with a view to explaining the relevance and uses of political economy analysis. It is intended to be used by a wide range of DFID programme managers and advisers, as well as staff in other HMG departments and partner organisations. The main questions it addresses are: ?? what is political economy analysis? ?? how and why does political economy analysis add value to DFID work? ?? what approaches and tools are available? ?? how should the analysis be prepared, undertaken and applied to DFID’s work? ?? how should we work with other development partners and across HMG on analysis? Key messages include: Political economy analysis is central to the formulation of sound country plans and sector programmes, and can play a key role in risk mitigation and ensuring that donors avoid harmful practices. Political economy analysis can help to improve development effectiveness by identifying how and where donors should focus efforts to promote positive change. There are a growing number of operationally relevant tools which can be used to inform development strategies at the country or sector level, or in relation to particular development problems. Several DFID country offices have used political economy analysis to improve the quality and impact of aid. This experience provides valuable lessons that should be considered when commissioning and undertaking political economy analysis. Where possible, analysis should be conducted on an ongoing basis with key partners in HMG and the wider development community to encourage shared understanding and joint action.